2001
DOI: 10.1046/j.1432-1327.2001.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of secondary and tertiary structure changes in the gastric H+/K+‐ATPase by infrared spectroscopy

Abstract: Conformational changes occurring in the catalytic cycle of the H 1 /K 1 -ATPase were monitored by Fourier transform infrared spectroscopy (FTIR). Caged compounds were used to release ATP, in the presence of Ca 21 , to induce the transition between the E1 and E1-P conformation of the H 1 /K 1 -ATPase. In addition to bands associated with the photolysis of the caged compounds, some peaks of the difference infrared spectra were associated with changes in secondary structure and modifications of the ionization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…These results indicate that while 516 residues belong to the fast exchanging class ( k =0.5 min −1 ) in the absence of ligand, only 185 remain in this class in the presence of 2 m M Ca‐ATP. This huge difference can only be explained in term of domain–domain interactions since the secondary structure of the protein does not change significantly in these conditions 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that while 516 residues belong to the fast exchanging class ( k =0.5 min −1 ) in the absence of ligand, only 185 remain in this class in the presence of 2 m M Ca‐ATP. This huge difference can only be explained in term of domain–domain interactions since the secondary structure of the protein does not change significantly in these conditions 14…”
Section: Resultsmentioning
confidence: 99%
“…1 H/ 2 H exchange kinetics has also been widely used in the field of membrane proteins. It allows the characterization of the protein stability in different experimental conditions5–13 and of conformational changes relevant to enzyme activity 14–17. Recently, it has been shown that combining linear dichroism with 1 H/ 2 H exchange measurement allows the exchange rate to be recorded specifically for the oriented secondary structures in a membrane‐embedded protein 18.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting absorbance bands showed both similarities to those observed for Ca 2+ ATPase as well as completely unique spectral features. Similarly, another member of the P‐type family, the H + ,K + ATPase, which is responsible for acidifying the stomach, was isolated from hog gastric fundus and showed unique FTIR spectral features upon activation by caged ATP, although the major inward‐to‐outward facing transition (E1‐to‐E2) was not investigated …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another member of the P-type family, the H 1 ,K 1 ATPase, which is responsible for acidifying the stomach, [26] was isolated from hog gastric fundus and showed unique FTIR spectral features upon activation by caged ATP, although the major inward-to-outward facing transition (E1-to-E2) was not investigated. [27] Thus, while a few members of the P-type ATPase family occur at high enough concentration in the membrane to allow characterization by triggering in the native environment, the vast majority would have to be expressed from recombinant sources. For the P-type ATPases, only the Ca 21 ATPase transporter has been characterized in a purified form of the full-length protein from a recombinant source using FTIR spectroscopy.…”
mentioning
confidence: 99%
“…The time from the reconstitution of lyophilized protein to acquisition of the first spectrum was <60 s. Normally the spectra need to be recorded at 1min intervals during the first 10 min, but the interval for the kinetic scanning is changed to 5 min between 15-90 min and 10 min after 90 min. The total collection time for all spectra varied between different proteins depending on exchange rates (e.g., 3 h for lactose permease, > 48 h for bacteriorhodopsin) 61,62 . During data acquisition, the spectrum for each individual scan is displayed on the page.…”
mentioning
confidence: 99%